A methodology to determine size and shape of plots for sugarcane plantation - Chem, Adriana Cristina [UNESP]; Goncalves Vianna, Andrea Carla [UNESP]; Ramos, Romulo Pimentel [UNESP]; Fiorentino, Helenice de Oliveira [UNESP] (Univ Sao Paolo, 2019)
Brazil is the largest sugarcane producer in the world and the leader in the production of sugar and ethanol. Although sugarcane has become an important factor in the Brazilian economy, cultivation has presented many issues, for example, the problems due to burning before the manual harvest. The Brazilian authorities have approved a law that prohibits this practice and mechanized harvesting has thus become the most fitting approach. Given this development, areas for sugarcane plantation must be properly rebuilt to accommodate the new way of harvesting. The main characteristic demanded of sugarcane plots to use harvesting machines is that they must be rectangular. In the present paper, we propose a methodology for dividing the plantation area into plots and planning their allocation so as to accommodate mechanized harvesting. In view of the requirement for plots to be rectangular, we represented this problem as a two-dimensional cutting problem, and to find a solution we adopted the AND/OR graph approach. The computational experiments were conducted using real cases, and the proposed strategy was shown to perform well.
Keywords: planting planning; sugarcane culture; mechanized harvesting; AND/OR graph approach